Early versus delayed enteral nutrition in critically ill children under 12 years of age: A systematic review and meta-analysis of randomised controlled trials - Marianne E. Visser; Roselyn Chipojola; Sarah Gordon; Amanda Brand; Nyanyiwe Mbeye; Gertrude Kunje; Talitha Mpando; Suzgika Lakudzala; Elodie Besnier; Celeste E. Naude (Clinical Nutrition Open Science)
Summary: Background & aims: Enteral nutrition (EN) is key to reducing malnutrition risk in critically ill children, with timing of EN initiation being an important consideration. This systematic review aimed to assess the effects of early enteral nutrition (EEN) compared to delayed enteral nutrition (DEN) in critically ill children as part of the Global Evidence, Local Adaptation (GELA) project. Methods: We searched PubMed, Embase and two trial registries (January 2000–November 2023) and included randomised controlled trials (RCTs) comparing EEN (typically within 24–48 hours of admission) to DEN (typically >48 hours of admission) in children aged one month to 12 years, and excluding studies in children with severe acute malnutrition, or conditions requiring long-term EN. Guided by Cochrane methods, we conducted random-effects meta-analyses to obtain pooled effect estimates for outcomes selected by the guideline development group, assessed risk of bias using Cochrane's Risk-of-Bias-2 tool and assessed certainty of the evidence using Grading of Recommendations, Assessment, Development and Evaluation (GRADE). Results: Four RCTs randomising 899 children in critical care settings in India, Iran and USA were included. Overall risk of bias was assessed as ‘high risk’ or ‘some concerns’ for all outcomes. Low-certainty evidence suggests that EEN may reduce in-hospital mortality (absolute effect (AE) 53 fewer deaths per 1000, 95% CI -85 to -12, I2=0%, 3 RCTs, n=869) and length of hospital stay on average (mean difference (MD) -2.98 days, 95% CI -9.79 to 3.83, I2=0%, 2 RCTs, n=760) compared to DEN, and may result in little to no difference in nosocomial infections (wound and blood stream infections) (AE 5 fewer cases per 1000, 95% CI -52 to 52, I2=0%, 3 RCTs, n=869). Evidence is very uncertain about effects on length of paediatric intensive care unit stay, number of days on the ventilator, sepsis, ventilator-associated pneumonia, and time to wound healing. Conclusion: EEN may reduce in-hospital mortality and length of hospital stay in critically ill children, but our confidence in the effect estimates is limited. More high-quality studies comparing EEN to DEN in relation to patient-relevant and clinically important outcomes in paediatric critical illness are needed. Prospective registration: PROSPERO CRD42023487325.